Effects of MicroRNA-195-5p on Biological Behaviors and Radiosensitivity of Lung Adenocarcinoma Cells via Targeting HOXA10. (7th December 2021) - Yuan, Cheng; Bai, Rui; Gao, Yanping; Jiang, Xueping; Li, Shuying; Sun, Wenjie; Li, Yangyi; Huang, Zhengrong; Gong, Yan; Xie, Conghua
Abstract : Objective . To explore the effects of miR-195-5p and its target gene HOXA10 on the biological behaviors and radiosensitivity of lung adenocarcinoma (LUAD) cells. Methods . The effects of miR-195-5p on LUAD cell proliferation, migration, invasion, cycle arrest, apoptosis, and radiosensitivity were investigated by in vitro experiments. The bioinformatics analysis was used to assess its clinical value and predict target genes. Double-luciferase experiments were used to verify whether the miR-195-5p directly targeted HOXA10. A xenograft tumor-bearing mouse model was used to examine its effects on the radiosensitivity of LUAD in vivo . Results . Both gain- and loss-of-function assays demonstrated that miR-195-5p inhibited LUAD cell proliferation, invasion, and migration, induced G1 phase arrest and apoptosis, and enhanced radiosensitivity. Double-luciferase experiments confirmed that miR-195-5p directly targeted HOXA10. Downregulation of HOXA10 also inhibited LUAD cell proliferation, migration, and invasion, induced G1 phase arrest and apoptosis, and enhanced radiosensitivity. The protein levels of β -catenin, c-myc, and Wnt1 were decreased by miR-195-5p and increased by its inhibitor. Moreover, the effects of the miR-195-5p inhibitor could be eliminated by HOXA10-siRNA. Furthermore, miR-195-5p improved radiosensitivity of LUAD cells in vivo . Conclusion . miR-195-5p has excellent antitumor effects via inhibiting cancer cell growth, invasion, and migration, arresting the cell cycle, promoting apoptosis, and sensitizing LUAD cells to X-ray irradiation by targeting HOXA10. Thus, miR-195-5p may serve as a potential candidate for the treatment of LUAD.